The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1017/s1463423618000373
|View full text |Cite
|
Sign up to set email alerts
|

Using formative research with older adults to inform a community physical activity programme: Get Healthy, Get Active

Abstract: Between March and June 2016, 34 participants took part in one of six focus groups as part of a descriptive formative study. A homogenous purposive sample of 28 community dwelling white, British older adults (six male), aged 65-90 years (M=78, SD=7 years) participated in one of five focus group sessions. An additional convenience pragmatic sub-sample of six participants (three male), aged 65-90 years (M=75, SD=4 years), recruited from an assisted living retirement home participated in a sixth focus group. Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 83 publications
(119 reference statements)
1
17
0
1
Order By: Relevance
“…Consistent with the literature, we found that health issues operated as both barriers and enablers to PA (12,(25)(26)(27). Well-designed PA programs beneficial to the management of health issues, combined with educational messages about the health benefits of PA, will facilitate older adults to overcome health-related barriers to actively participate in PA (1).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with the literature, we found that health issues operated as both barriers and enablers to PA (12,(25)(26)(27). Well-designed PA programs beneficial to the management of health issues, combined with educational messages about the health benefits of PA, will facilitate older adults to overcome health-related barriers to actively participate in PA (1).…”
Section: Discussionsupporting
confidence: 86%
“…and enablers (e.g., having a fulfilling life, having more time after retirement, and pro-exercise culture). We only identified one empirical study reporting that older age and disinterest were barriers to PA (26). More empirical research is needed to establish the evidence on these newly identified barriers and enablers to PA in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of data analysis is described in Table 3; based on (Sibeoni et al, 2017, p. 49;Sanders et al, 2019).…”
Section: Process Of Inductive Thematic Analysismentioning
confidence: 99%
“…Evidence generated from the Get Healthy Get Active programme mapped against the intended outcomes. Notes:1Get Active Get Healthy, what we have learned so far[34], Tackling Inactivity[43], 2Design Principles[44], 3Sport England Evaluation Framework[45], 4Hertfordshire Evaluation Framework[49], 5Examples of publications include[50][51][52][53][54][55][56][57][58][59][60] Fynn et al International Journal of Behavioral Nutrition and Physical Activity (2021) 18:31…”
mentioning
confidence: 99%